Chat with our AI personalities
Assume f=f(x), g=g(x)and (f^-1)(x) is the functional inverse of f(x). (f+g)'=f'+g' (f*g)'=f'*g+f*g' product rule (f(g))'=g'*f'(g) compositional rule (f/g)'=(f'*g-f*g')/(g^2) quotient rule (d/dx)(x^r)=r*x^(r-1) power rule and applies for ALL r. where g^2 is g*g not g(g)
1 g = 1000 mg1 g = 1000 mg1 g = 1000 mg1 g = 1000 mg1 g = 1000 mg1 g = 1000 mg
1 g = 0.001 kg1 g = 0.001 kg1 g = 0.001 kg1 g = 0.001 kg1 g = 0.001 kg1 g = 0.001 kg
The set notation for G would be written as G = {...}, where the ellipsis (...) represents the elements of the set G.
We will call the golden ratio, 1.618033989:1, G. G2-1=G; 1/G+1=G; (1+G)/G=G; For more, research golden ratio on wikipedia.